Evaluation of the Safety of the Way Sekampung Bridge Against Extreme Flooding for the 50 Year Return Period - Al Rasyid, Burhan Najib; Purwadi, Ofik Taufik; Tugiono, Subuh; Zakaria, Ahmad (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The purpose of this study is to evaluate the Sekampung Way Bridge, which is located on the Sumatra Cross Road on the border between Bumi Agung Village in Tegineneng District, Pesawaran and Mandah Village in Natar District, South Lampung, with coordinates 105°10'33.75